2018
DOI: 10.13057/biodiv/d190411
|View full text |Cite
|
Sign up to set email alerts
|

Habitat of Nepenthes spp. in the area of Sampit Botanic Gardens, Central Kalimantan, Indonesia

Abstract: Hidayat S, Dodo, Purnomo DW, Helmanto H, Supriyatna I. 2018. Habitat of Nepenthes spp. in the area of Sampit BotanicGardens, Central Kalimantan, Indonesia. Biodiversitas 19: 1258-1265. Nepenthes spp are protected plant and most of them are at leastconcern criteria. The research purpose is to explore the habitat information that supports the existence of Nepenthes in the area aroundSampit Botanic Gardens, Central Kalimantan. Three different sites have been selected in this research. In each sites, seven samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Among the species of Nepenthes, this species was the most widely distributed, stretching from Thailand, Indo-China, Peninsular Malaysia, through Indonesia, the Philippines, New Guinea to Australia, and this species usually grows abundantly in swamp (Adam et al 1992). In Bangka Belitung Province, N. mirabiilis was also found in swamp forest (Rizqiani et al 2018), and in peat swamp of Borneo, N.mirabilis was also the dominant climber (Hidayat et al 2018). In Halmahera Island, N. mirabilis was found in lowland forest and edge of swamp (Cahyono et al 2019).…”
Section: Shrubs and Herbsmentioning
confidence: 98%
“…Among the species of Nepenthes, this species was the most widely distributed, stretching from Thailand, Indo-China, Peninsular Malaysia, through Indonesia, the Philippines, New Guinea to Australia, and this species usually grows abundantly in swamp (Adam et al 1992). In Bangka Belitung Province, N. mirabiilis was also found in swamp forest (Rizqiani et al 2018), and in peat swamp of Borneo, N.mirabilis was also the dominant climber (Hidayat et al 2018). In Halmahera Island, N. mirabilis was found in lowland forest and edge of swamp (Cahyono et al 2019).…”
Section: Shrubs and Herbsmentioning
confidence: 98%
“…Low-pH peat swamp consisting of constantly flooded ground [13]. In their natural habitat, most Nepenthes are either vines or small shrubs that attach themselves to other plants by means of looped tendrils that sprout from the tips of their leaf blades [12]. Remarkably, at least nine Nepenthes taxa were found outside the sampling plots in AHUFR.…”
Section: Other Notable Non-timber Species Outside the Sampling Plotsmentioning
confidence: 99%
“…This is clearly due to the habitat for each species, in which N. rafflesiana occurs at the ridge area, while N. ampullaria and N. gracilis were found in the lower area (swales). The occurrence of N. ampullaria and N. gracilis in the wetter area such as peat swamp forests are common (Clarke 2001;Hidayat et al, 2018). However, the previous study has demonstrated that both species, N. ampullaria and N. gracilis, can be found widespread in dry or less inundated area (Adam et al, 2009).…”
Section: Relationships Between the Abundance Of Nepenthes And Soil Parametersmentioning
confidence: 99%